DNA Interaction: The Structure of Short and Genomic DNA at the Interparticle Junctions of Cationic Nanoparticles (Adv. Mater. Interfaces 17/2017). Issue 17 (8th September 2017) - Gisbert‐Quilis, Patricia; Masetti, Matteo; Morla‐Folch, Judit; Fitzgerald, Jamie M.; Pazos‐Perez, Nicolas; Garcia‐Rico, Eduardo; Giannini, Vincenzo; Alvarez‐Puebla, Ramon A.; Guerrini, Luca
Abstract : In article number1700724 Ramon A. Alvarez‐Puebla, Luca Guerrini, and co‐workers investigate the strand separation of nucleic acid duplexes at the junctions of cationic nanoparticle clusters by combining plasmon‐based spectroscopies and theoretical simulations. Geometrical organization and size distribution of the clusters, as well as nanoparticle surface charge play major roles in determining the extent of the double‐helix dissociation.